Seasonal Prevalence of Helminthic Infections in the Gastrointestinal Tract of Sheep in Mazandaran Province, Northern Iran - Alireza Salehi; Mahsa Razavi; Nasrollah Vahedi Nouri (Journal of Parasitology Research)
Helminthic infection is the major cause of the sheep’s reduced productivity. In this study, a total number of 240 fecal samples of sheep from stationary flocks of four different zones of Mazandaran province (Amol, Babol, Sari, and Nowshahr cities) were examined each season, out of which 53.33% of animals were affected by the helminthic infections. The most prevalent infecting parasites were the Trichostrongylidae (46.61%), followed by the Fasciola (9.96%). In addition, the Strongyloides had the lowest proportion with only 2.39%. The other detected parasites included Chabertia (5.98%), Cooperia (3.19%), Nematodirus (3.19%), Trichuris (5.58%), Toxocaridae (4.78%), Haemonchus (4.78%), Ostertagia (5.58%), Oesophagostomum (4.78%), and Dicrocoelium (3.19%). The nematodes had the highest percentage with 86.85%, whereas the trematodes followed them with 13.15%. No significant difference was observed between the infection level in females and males, with 56.9% and 43.94% rates of infection, respectively. Significantly lower infection was observed in winter compared with the other seasons. Trichostrongylidae was the dominant genus across all seasons. It was also noted that winter had the lowest percentage of helminthic infection significantly. The eggs per gram of feces was also estimated, and it showed that a significant number of sheep are infected with a moderate number of parasites. In a conclusion, even though livestock farmers have been using antiparasitic drugs in their livestock in recent years, parasitic infection still exists in livestock. Thus, a proper implementation of helminthic infection control programs in this area should be employed as the key element for reducing the high prevalence of livestock helminthic infection.